2022
DOI: 10.3389/fmicb.2022.855473
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ectomycorrhizal Symbiosis Behind the Host Plants Ameliorated Tolerance Against Heavy Metal Stress

Abstract: Soil heavy metal (HM) pollution, which arises from natural and anthropogenic sources, is a prime threat to the environment due to its accumulative property and non-biodegradability. Ectomycorrhizal (ECM) symbiosis is highly efficient in conferring enhanced metal tolerance to their host plants, enabling their regeneration on metal-contaminated lands for bioremediation programs. Numerous reports are available regarding ECM fungal potential to colonize metal-contaminated lands and various defense mechanisms of EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 138 publications
(171 reference statements)
0
10
0
Order By: Relevance
“…The Pb absorbed by T . borchii hyphae seems not to have accumulated in the mantle as suggested by some works (Chot & Reddy, 2022) but transferred towards the Hartig net where Pb was found more visible by staining with sodium rhodizonate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The Pb absorbed by T . borchii hyphae seems not to have accumulated in the mantle as suggested by some works (Chot & Reddy, 2022) but transferred towards the Hartig net where Pb was found more visible by staining with sodium rhodizonate.…”
Section: Discussionmentioning
confidence: 62%
“…However, the presence of Pb in soil may interfere with the symbiosis establishment, hindering the plant-fungus recognition or slowing down the root colonization. The negative effect of Pb and other heavy metals on the abundance of ectomycorrhizas was already demonstrated by different authors (Bojarczuk & Kieliszewska-Rokicka, 2010;Chappelka et al, 1991;Ouatiki et al, 2021).…”
Section: Discussionmentioning
confidence: 69%
“…At present, ECMF assisted phytoremediation of HM contaminated soil has been shown to be an efficient and clean remediation method, and has increasingly been used for remediation of HM contaminated soil ( Colpaert et al., 2011 ; Sousa et al., 2011 ; Heinonsalo et al., 2015 ; Chot and Reddy, 2022 ; Oladoye et al., 2022 ). However, previous studies have shown that not all fungal species were able to effectively maintain the adaptability of host plants under HM stress ( Kushwaha et al., 2015 ; Ayangbenro and Babalola, 2017 ; Chot and Reddy, 2022 ).It is interesting that most studies have explored the impact of mycorrhizal fungi on host plant metal tolerance mainly through the study of tolerant strains ( Adriaensen et al., 2006 ; Colpaert et al., 2011 ; Ma et al., 2014 ; Heinonsalo et al., 2015 ), while strains without or little tolerance to HMs tolerance have received little attention. For example, tolerant ecotypes may act as a better filter than non-tolerant ecotypes because the former more strongly prevent metals to transfer to their host ( Colpaert et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metal elements include essential and non-essential elements. Essential metals are required for many physiological processes in living organisms, such as zinc, manganese and copper, non-essential metals are cadmium, lead or mercury [52][53][54][55][56][57][58][59][60][61][62]. Zhang et al found that overexpressing miR156 accumulated significantly less Cd in their branches and showed enhanced tolerance to Cd stress in plants.…”
Section: For Mirna and Heavy Metals Stressmentioning
confidence: 99%